ta có \(\left(x+2\right)^2-2\left(x+2\right)\left(x+3\right)+\left(x+5\right)^2=7\)
\(\Leftrightarrow x^2+4x+4-2\left(x^2+5x+6\right)+x^2+10x+25=7\)
\(\Leftrightarrow4x+10=0\Leftrightarrow x=-\frac{5}{2}\)
Bạn áp dụng hằng đẳng thức số 1, nhân phá ngoặc là Ok nhé
\(\left(x+2\right)^2-2\left(x+2\right)\left(x+3\right)+\left(x+5\right)^2=7\)
\(\Leftrightarrow x^2+4x+4-2\left(x^2+3x+2x+6\right)+x^2+10x+25-7=0\)
\(\Leftrightarrow2x^2+14x+22-2x^2-6x-4x-12=0\)
\(\Leftrightarrow4x+10=0\)
\(\Leftrightarrow4x=-10\)
\(\Leftrightarrow x=\frac{-5}{2}\)
Trả lời:
( x + 2 )2 - 2 ( x + 2 ) ( x + 3 ) + ( x + 5 )2 = 7
<=> x2 + 4x + 4 - 2 ( x2 + 5x + 6 ) + x2 + 10x + 25 = 7
<=> x2 + 4x + 4 - 2x2 - 10x - 12 + x2 + 10x + 25 = 7
<=> 4x + 17 = 7
<=> 4x = - 10
<=> x = - 5/2
Vậy x = - 5/2 là nghiệm của pt.
(x+2)2 - 2(x+2)(x+3)+(x+5)2=7
\(\Leftrightarrow\)x2+4x+4 - (2x+4)(x+3)+x2 +10x +25 - 7=0
\(\Leftrightarrow\)2x2 + 14x+22 -(2x2+6x+4x+12)=0
\(\Leftrightarrow\)2x2+14x+22- 2x2- 6x- 4x- 12=0
\(\Leftrightarrow\)4x= -10
\(\Leftrightarrow\)x= \(\frac{-10}{4}\)
Vậy x =\(\frac{-10}{4}\)